A Study on the Rise and Recent Development in UPI (Unified Payments Interface) - Verma, Bhumi; Purohit, Mihir; Vidani, Jignesh (MultiTech Publisher, 2024)
The Unified Payments Interface (UPI) has emerged as a transformative force in India's digital payments sphere, redefining financial transactions and bolstering financial inclusion. UPI's hallmark lies in its seamless, secure, and interoperable platform facilitating instant money transfers across diverse bank accounts. This simplicity has not only eradicated the reliance on cash but has also eliminated the complexities associated with traditional banking procedures, particularly benefiting unbanked and underbanked individuals.The impact of UPI extends beyond mere transactions; it has substantially diminished cash dependency, fostered transparency, and catalyzed economic growth. This, in turn, has empowered small businesses and micro-entrepreneurs, closing the gap in financial literacy, and bridging the digital divide between rural and urban areas. UPI's rise has prompted a paradigm shift in the banking sector, compelling institutions to embrace digital-first strategies, customize offerings, and streamline branch networks. Furthermore, it has created lucrative opportunities for banks through fee-based services and strategic collaborations with Fintech startups. Looking ahead, UPI's future appears promising, with the integration of cutting-edge technologies like blockchain and AI poised to reshape the financial landscape. However, inherent challenges persist, including data privacy apprehensions, regulatory adjustments, and the imperative need for long-term financial sustainability. In conclusion, UPI's indelible mark on India's digital payment ecosystem underscores its undeniable impact. Continued innovation, coupled with a robust regulatory framework, is pivotal for UPI to steer India towards a truly cashless and financially inclusive future